Waste Analysis in Herbal Oil Product Packaging Using the Lean Six Sigma Method: Analisis Pemborosan pada Pengemasan Produk Minyak Herbal Menggunakan Metode Lean Six Sigma - Dama Yanti, Alviani; Rochmoeljati, Rochmoeljati (Academia Open, 2026)
General Background: Production inefficiencies in pharmaceutical manufacturing are frequently associated with process waste and packaging defects that reduce operational performance and product quality. Specific Background: In herbal oil production, the outer packaging stage exhibited recurring defects, motion waste, and overprocessing activities that increased lead time and generated non-value-added activities. Knowledge Gap: Previous studies on Lean, Six Sigma, and Lean Six Sigma have predominantly focused on general manufacturing industries and rarely integrated Value Stream Mapping, VALSAT, Fishbone Diagram, and Failure Mode and Effect Analysis within a comprehensive DMAIC framework for pharmaceutical herbal packaging processes. Aims: This study aims to identify dominant waste types, analyze the root causes of packaging defects, and formulate improvement recommendations using an integrated Lean Six Sigma DMAIC approach. Results: The findings indicate that the dominant wastes were defect, motion, and overprocessing. The major packaging defects consisted of wrinkled labels, untidy individual bottle wrapping, and perforated group packaging, with untidy individual bottle wrapping showing the highest Risk Priority Number of 294. The proposed improvements eliminated non-value-added activities and reduced necessary non-value-added activities, decreasing production lead time from 7,497.4 minutes to 5,382.4 minutes while increasing Process Cycle Efficiency from 26.89% to 37.46%. The process achieved a sigma level of 3.59 with an average DPMO of 18,016. Novelty: This study integrates Lean Six Sigma DMAIC with VSM, VALSAT, PAM, Fishbone Diagram, and FMEA to provide a structured risk-based evaluation of waste and defects in herbal oil packaging operations. Implications: The results demonstrate that systematic waste reduction and defect mitigation support higher production efficiency and operational performance in pharmaceutical manufacturing. Highlights: Defect, motion, and overprocessing emerged as the dominant production waste categories. Risk evaluation identified untidy individual bottle wrapping as the highest-priority failure mode. Proposed process changes shortened manufacturing duration and raised Process Cycle Efficiency. Keywords: Lean Six Sigma, DMAIC, FMEA, Herbal Oil Packaging, Process Cycle Efficiency